O'Reilly velocity web performance & operations conference - Safari eBooks; O'Reilly velocity web performance & operations conference (2011 : Santa Clara, Calif.) (Santa Clara, CA : O'Reilly, 2011)
"Discover the latest tools, skills, and ideas in web operations and performance with this complete video compilation of O'Reilly's Velocity Conference 2011. Held on June 14-16 in the heart of California's Silicon Valley, Velocity 2011 included 68 inspiring sessions and workshops with the leading practitioners in the world of web ops. Watch luminaries such as John Allspaw, Mark Burgess, Rachel Chalmers, and Douglas Crockford lead sessions in four tracks: Operations, Web Performance, Velocity Culture, and Mobile Performance. Download these videos or view them through our HD player, and learn how to improve your online presence and performance."--Resource description page.
Title and publication information from title screen (viewed Sept. 2, 2011).
Recorded at O'Reilly velocity web preformance & operations conference: June 14-16,2011, Santa Clara, CA.
Keywords: Internet programming; Web site development; Web sites -- Design; Web search engines; Electronic books